Stress Diminishes BDNF-stimulated TrkB Signaling, TrkB-NMDA Receptor Linkage and Neuronal Activity in the Rat Brain. (1st October 2021) - Robinson, Siobhan; Mogul, Allison S.; Taylor-Yeremeeva, Elisa M.; Khan, Amber; Tirabassi, Anthony D.; Wang, Hoau-Yan
Highlights: Acute or repeated stress diminishes BDNF-stimulated TrkB signaling in HIPPO and PFC. TrkB-NMDAr linkage is differentially affected by stress in HIPPO versus PFC. BDNF-stimulated Arc expression in HIPPO and PFC is diminished by repeated stress. Repeated stress elevates pro-inflammatory cytokine levels in HIPPO and PFC. Abstract: Exposure to intense or repeated stressors can lead to depression or post-traumatic stress disorder (PTSD). Neurological changes induced by stress include impaired neurotrophin signaling, which is known to influence synaptic integrity and plasticity. The present study used an ex vivo approach to examine the impact of acute or repeated stress on BDNF-stimulated TrkB signaling in hippocampus (HIPPO) and prefrontal cortex (PFC). Rats in an acute multiple stressor group experienced five stressors in one day whereas rats in a repeated unpredictable stressor group experienced 20 stressors across 10 days. After stress exposure, slices were incubated with vehicle or BDNF, followed by immunoprecipitation and immunoblot assays to assess protein levels, activation states and protein–protein linkage associated with BDNF-TrkB signaling. Three key findings are (1) exposure to stressors significantly diminished BDNF-stimulated TrkB signaling in HIPPO and PFC such that reductions in TrkB activation, diminished recruitment of adaptor proteins to TrkB, reduced activation of downstream signaling molecules, disruption of TrkB-NMDAr linkage, and changes in basal and BDNF-stimulated Arc expression were observed. (2) After stress, BDNF stimulation enhanced TrkB-NMDAr linkage in PFC, suggestive of compensatory mechanisms in this region. (3) We discovered an uncoupling between TrkB signaling, TrkB-NMDAr linkage and Arc expression in PFC and HIPPO. In addition, a robust surge in pro-inflammatory cytokines was observed in both regions after repeated exposure to stressors. Collectively, these data provide therapeutic targets for future studies that investigate how to reverse stress-induced downregulation of BDNF-TrkB signaling and underscore the need for functional studies that examine stress-related TrkB-NMDAr activities in PFC.